The Special Delivery Unit: A Novel Concept for Mother–Baby Continuity for Major Fetal Abnormalities - Moise, Kenneth J., Jr.; Bebbington, Michael W.; Nix, Michael; Thomas, Heather; Kosko, Andrew (American Journal of Perinatology, 2023)
Objective This article describes the experience in the planning and development of a special delivery unit (SDU) at our free-standing children's hospital in Austin, Texas.Study Design Description of various aspects of the development of the SDU. In addition, telephone surveys were obtained from five other institutions regarding the planning and current status of their SDUs.Results Since the advent of the SDU at Children's Hospital of Philadelphia in 2008, several free-standing children's hospitals have opened similar units at their institutions. Developing an obstetrical unit in a children's hospital can be a daunting task on many fronts. The costs of providing 24-hour obstetrical, nursing, and anesthesiology coverage must be considered. Although most SDUs are associated with a fetal center and fetal surgery/interventions, some units function exclusively for the delivery of pregnancies complicated by major fetal conditions where the neonate will require immediate surgical care or other interventions.Conclusion Research on the cost-effectiveness and the effect of SDUs on clinical outcome, teaching, and patient satisfaction is warranted.Key Points
Keywords: fetal anomalies; special delivery unit; SDU; children's hospital; free-standing children's hospital; fetal center; fetal intervention